Development Communication and Present Trends in Printing Media - Maram Srinivas (International journal of economic perspectives, 2022)
Development communication is communication used for human development. Both print media and electronic media play an important role in the development of any country. In India, the government uses print media to secure wide coverage of messages through various newspapers and magazines. Print media as a traditional medium plays an important role in the development of communication. In India, the strength of the print media is largely linked to its historical experience and particularly to the freedom struggle as well as movements for social emancipation, reform and reform. Today various modern and sophisticated technologies are using print media in both developed and less developed countries and they are also facing stiff competition from electronic media. This article studies the circulation trends of print media: newspapers and magazines in India and some other countries and also discusses how the role of print media is changing in development communication in recent times. It also focuses on the impact of new electronic media on print media.